(untitled) - Greene, Mark (Great Britain, 2016)
This beautiful illustrated tribute focuses on the Queen$1 (Bs own words to draw out the central role of her trust in Jesus Christ in shaping her life and work, offering us an inspiring, multi-faceted insight into a life well lived for others.s
Keywords: the King